Studi Kelayakan Pembangunan Gedung Factory Sharing di Kota Pangkalpinang - Junita Eka Susanti (Universitas Islam Raden Rahmat, Malang, 2024)
Pangkalpinang City has great potential in the fisheries and marine sector, which can be encouraged by support from small and medium industries. One of the proposed solutions is the development of standardized Factory Sharing to increase production efficiency and reduce operational costs. This study methodology uses a feasibility study, which includes technical, economic, and environmental analysis. Data was collected through field surveys and interviews, as well as reviewing RTRW documents and local economic data. The research results obtained technically show that land for development is available without the need for development but requires increased road access and clean water networks. From an economic perspective, this project is very profitable, with a positive NPV value of IDR 27,712,225,238 and an IRR of 20%, far exceeding the discount rate of 5.75%. From an environmental aspect, this project complies with the RTRW and requires an environmental impact assessment to ensure compliance with standards. Overall, the Factory Sharing development project was declared feasible to implement.